Needlescopic primary paediatric inguinal hernia repair by hernia sac disconnection and peritoneal closure - Mohamed Abdelmoniem Elhosary; Akram Mohammad Elbatarny; Mohamed Ahmed Arafa; Sherif Medhat Mahmoud; Khalid Ahmed Ismail; Khalid Mohamed Elshimy (Journal of the Pakistan Medical Association, 2023)
N/A